The Synthesis of Rigid Chromophore–Spacer–Chromophore Dyads and Three-Armed Triads by the 1,3-Dipolar Reaction of Cyclobutene Epoxides with Aromatic Dipolarophiles - Margetić, Davor; Butler, Douglas N.; Warrener, Ronald N. (Synthesis, 2013)
A series of polyaromatic hydrocarbons (PAHs) or their aza derivatives were reacted as dipolarophiles with ring-fused cyclobutene epoxides (CEs) in the 1,3-dipolar cycloaddition protocol to form 1:1 cycloadducts. The dihydroforms of the PAH chromophores contained in the rigid alicyclic scaffold were dehydrogenated to regenerate the original PAH chromophore and constituted a new route to rigid chromophore-nσ-PAH dyads separated by an alicyclic scaffold. The anthracene 1:1 adduct derived from the reaction with the 5,8-dimethoxynaphthalene-containing CE was reacted a second time to produce stereoisomeric three-armed triads in which naphthalene chromophores were attached rigidly onto scaffold. Two approaches were used to generate the incipient cyclic 1,3-dipolar intermediates involved in cycloaddition process. The first method employed ring-opening of functionalised CEs, the other method produced the dipolar reagent in situ by loss of dinitrogen from the initially formed adduct resulting from treatment of fused norbornenes with 2,5-bis(trifluoromethyl)-1,3,4-oxadiazole.
Keywords: cycloaddition; arenes; ylides; polycycles; dehydrogenation